Viewer's Perception of The Religious Dialogue "Boris Beragama Bikin Histeris" on Youtube Media Using SNA Analysis - Pramesti Sekar Hapsari; Resman Muharul Tambunan (Metacommunication: Journal of Communication Studies, 2024)
The reality of religious pluralism is a challenge faced by every religious follower. Religious dialogue is an effective mechanism in creating racial and religious unity. This research discusses religious dialogue in the #LogIndiCloseTheDoor content episode "Boris Beragama Bikin Histeris" on YouTube. This content received various responses from the audience because it featured presenters from different religious backgrounds, namely Habib Jafar, Onadio Leonardo and Boris Bokir who discussed religion lightly. This research uses William Gamson and Andre Modigliani's framing theory based on the Network Analysis (SNA) method. The research analyzed 10 actors with the largest communication network population. The results show that the actors have positive comments based on the three groups formed, namely, content, host and guest stars and religion. The first group, content has positive results based on content that focuses on religious tolerance. The second group, hosts and guest stars produce positive perceptions based on the personalities of the hosts and guest stars in the content and the third group, religion which has positive results based on religious content that the hosts and guest stars bring.